Differentially expressed genes in head kidney of Pelteobagrus fulvidraco following Vibrio cholerae challenge - Jiang, Sen-Hao; Wu, Lin-Xin; Cai, Yu-Ting; Ma, Rui-Ting; Zhang, Hua-Bin; Zhang, Dai-Zhen; Tang, Bo-Ping; Liu, Qiu-Ning; Dai, Li-Shang (Frontiers in Immunology, 2023)
The yellow catfish (Pelteobagrus fulvidraco) is a freshwater fish with high economic value in eastern China. Nevertheless, pathogens causing bacterial diseases in P. fulvidraco have brought about huge economic loss and high mortality in artificial aquaculture. For disease control, it is critical to further understand the immune system of yellow catfish and immune-related genes with which they respond to pathogenic infections. In this study, high-throughput sequencing methods were used to analyze the transcriptomic spectrum of the head kidney from P. fulvidraco challenged by Vibrio cholera. A total of 45,544 unique transcript fragments (unigenes) were acquired after assembly and annotation, with an average length of 1,373 bp. Additionally, 674 differentially expressed genes (DEGs) were identified after stimulation with V. cholerae, 353 and 321 genes were identified as remarkably up- or downregulated, respectively. To further study the immune-related DEGs, we performed KEGG enrichment and GO enrichment. The results showed gene regulation of response to stimulus, immune response, immune system progress, response to external stimuli and cellular response to stimuli. Analysis of KEGG enrichment is important to identify chief immune related pathways. Real-time quantitative reverse transcription-PCR (qRT-PCR) results indicated 10 immune response genes that were found to be upregulated compared to a control group after 6 h of V. cholerae challenging. In summary, the results of our study are helpful to determine the defense mechanisms and immune system responses of yellow catfish in reaction to bacterial challenges.